Periodo explícito, periodo continuo y valorización de una empresa - Pacheco Mexzon, Raimundo Renaun (2012)
The company as a going concern generated funds. Therefore when you want to determine its market value should be considered a historical period (the past), present (today) and future period (after today). In the future period should be considered an explicit period and a sustained period. The explicit term future must consider more than 5 years and the future continuous period from year 6. In this context we try to calculate the value of the company using the method of discounted cash flow. Hence, our concern is to propose a methodology for calculating the enterprise value based on the “discounted free cash flow.”